PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI DI FAKULTAS EKONOMI UNIVERSITAS JEMBER - Farida Hasan; Andi Sularso; Handriyono Handriyono (RELASI : JURNAL EKONOMI, 2016)
Based on the results of research in the Faculty of Economics, University ofJember on the influence of the physical work environment, organizational cultureand work motivation on employee performance This study used path analysis (PathAnalysis) with data processing using Statistical Product and Service (SPSS Versi.15)The results of the study show that the Physical Working Environment (X1), andCultural Organization (X2), the motivation of Work (Y1) simultaneously positive andsignificant effect on employee performance (Y2). This can be concluded when thefourth variable is certainly increased employee performance also increased.Physical Work Environment (X1) partially not significant effect on employeeperformance (Y2). But with the results of a positive coefficient of the workingenvironment then lambatlaun improve the performance of the company to generatebetter employment process takes long enough to be supported by a conduciveenvironment, the results of the work will be the maximum in accordance with thedesired company. Cultural Organization (X2) partially not significant effect onemployee performance (Y2). Good organizational culture will produce output that isalso good that the realignment of work habits do not tutas should be avoided.Motivation (Y1) partially positive and significant impact on employee performance(Y2). Motivation needs to be improved in an effort to stimulate the performance ofemployees, with rewards for the work that deserved the employee will improve itsperformance which will have a positive impact on the company.